KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN - Mahardhika, Mustafidah; Arintowati , Dyan (Universitas Nusantara PGRI Kediri, 2020)
After the Covid-19 pandemic ends, business competition is predicted to be very fierce. Business and industries are required to be able to implement marketing strategies so that consumers decide to buy products, both goods and services they sell. Some marketing strategies that can be used to make consumers decide to buy are by offering quality products, quality services, and determining the right pricing strategy. The purpose of this research is to determine the effect of product quality, service quality, and price on consumer buying decisions at BCA Cellular in Loceret District. This type of research is quantitative research. Data collection techniques by conducting interviews, documentation, and questionnaires. For data analysis using multiple linear regression analysis. Based on the results of the research data analysis, there are several results. The first result states that partially the price influences consumer buying decisions at BCA Cellular in Loceret District. The second result states that product quality and service quality do not influence consumer buying decisions at BCA Cellular in Loceret District. The third result states that product quality, service quality, and price simultaneously influence consumer buying decisions at BCA Cellular in Loceret District.